MODEL PENENTUAN TARIF MENGGUNAKAN MINIMISASI BIAYA DAN PERMINTAAN INPUT UNTUK PERUSAHAAN MONOPOLI - Fitra Waty (Universitas Negeri Medan, 2012)
Provision of some public goods, such as drinking water, electricity, gas, telephone, in many countries is generally done by the government. This is due to the firm is a natural monopoly, meaning that these companies require a huge investment, so that the level of efficiency can be achieved when the large scale of production. The problem is what price should be charged to the public? This study aimed to determine the price of a good in theory. The method used is minimization cost of production (through indirect cost function) with the constraints of the production function.